Strengthening Financial Governance in Islamic Schools: The Strategic Role of School Committees in Enhancing Transparency and Accountability - Meisya Nuryaspi Maulida; Moh.Sugandi; Gebran El Khoury (Mapendis: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the influence of Islamic transformational leadership on teacher discipline and work ethic at Madrasah Tsanawiyah Bagan Asahan. In the context of Islamic education, Islamic transformational leadership integrates modern leadership principles with Islamic values ​​based on trust, exemplary behavior, justice, and spiritual motivation. This study used a quantitative approach with a survey method of 30 teachers, and the data were analyzed using linear regression to test the influence between variables. The results showed that Islamic transformational leadership had a positive and significant effect on teacher discipline with a contribution of 39.9% and teacher work ethic by 46.4%. Simultaneously, Islamic transformational leadership contributed 55.5% to improving teacher discipline and work ethic. These findings indicate that the application of Islamic values ​​in leadership can simultaneously improve teacher discipline and work ethic. In conclusion, Islamic transformational leadership is effective in improving the quality of teacher discipline and work ethic in madrasahs, with important implications for the management of Islamic education based on spiritual and moral values.